2010
DOI: 10.1007/s11113-010-9190-1
|View full text |Cite
|
Sign up to set email alerts
|

A Matter of Number, Age or Marriage? Children and Marital Dissolution in Italy

Abstract: Family, Italy, Divorce, Marital dissolution, Children,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…They further showed evidence that fathers invest more in the family and spend more time when the first child is a son or when there are male children. Findings from other developed countries seem to align with the hypothesis that children's sex composition does not affect divorce risks (Leigh 2009;Tjøtta and Vaage 2003;Todesco 2011;Vignoli and Ferro 2009). Interestingly, some review papers tend to have swayed the argument in favour of a negative effect of having girl child/ren on risk of divorce (Lundberg 2005;Raley and Bianchi 2006).…”
Section: Review Of Empirical Evidencementioning
confidence: 55%
See 1 more Smart Citation
“…They further showed evidence that fathers invest more in the family and spend more time when the first child is a son or when there are male children. Findings from other developed countries seem to align with the hypothesis that children's sex composition does not affect divorce risks (Leigh 2009;Tjøtta and Vaage 2003;Todesco 2011;Vignoli and Ferro 2009). Interestingly, some review papers tend to have swayed the argument in favour of a negative effect of having girl child/ren on risk of divorce (Lundberg 2005;Raley and Bianchi 2006).…”
Section: Review Of Empirical Evidencementioning
confidence: 55%
“…Secondly, women with children may not easily gain entry into another marital union. This fear makes many women avoid divorce, knowing that with children, re-marriage is difficult (Diekmann and Schmidheiny 2004;Leigh 2009;Todesco 2011).…”
Section: Theoretical Perspectives and Hypothesesmentioning
confidence: 99%
“…Empirical studies have generally demonstrated a positive association between the presence of children and marital stability. Various studies in the US and European countries have found that, after accounting for the duration of marriage and other confounding variables, childlessness significantly elevates the risk of marital disruption (Berrington & Diamond, 1999;Morgan & Rindfuss, 1985;Andersson, 1997;Diekmann & Engelhardt, 1999, Todesco, 2011. There is, however, a non-linear relationship between the number of children and the risk of divorce.…”
Section: The Number Of Children Children's Age and Marital Dissolutionmentioning
confidence: 99%
“…Children born out of marriage with a different biological parent could have little or a negative effect on marriage stability. They are generally not considered a marital-specific capital, nor would they inspire a strong feeling of obligation from the non-biological parent (Todesco, 2011). Remarriages involving the presence of stepchildren have been shown to be more prone to disruption than those without stepchildren (Waite & Lillard, 1991).…”
Section: Stepchildren Premarital Conception and Marital Dissolutionmentioning
confidence: 99%
“…Findings also suggest that the ages of the children are an essential predictor of divorce, as people are reluctant to separate when they have young children. The likelihood of divorce has been found to be lowest when children are young and to rise as they age, although findings vary somewhat from country to country (Andersson 1997;Bernardi and Martínez-Pastor 2011;Hart et al 2017;Jalovaara 2001;Kalmijn and Poortman 2006;Todesco 2011;Twenge et al 2003;Vignoli and Ferro 2009).…”
Section: The Relation Between Children and Divorcementioning
confidence: 99%